Item-level and Composite-level Interrater Reliability of Functional Movement Screen™ Scores Following Condensed Training in Novice Raters - Brent A Harper; Stephen M Glass (North American Sports Medicine Institute, 2021)
# BACKGROUND The Functional Movement Screen™ (FMS™) is a clinical instrument designed to use movement behaviors to screen individuals for injury risk. Current rater certification programs focus on extensive, individualized training, which may not be appropriate in all screening contexts. # PURPOSE The purpose of this research was to examine the effect of a two-hour FMS^TM^ training seminar on measures of reliability between previously untrained scorers. # STUDY DESIGN Repeated measures, descriptive cohort study. # METHODS Four novice raters completed a two-hour training course administered by an FMS™-certified, licensed physical therapist. The novices and the instructor then scored a group of 16 individuals on the seven FMS™ component tests on two separate occasions. Interrater reliability was assessed for FMS™ component scores using Fleiss' kappa and Krippendorff's α. Interrater reliability for the FMS™ composite score was assessed using a two-way ICC for agreement (a priori significance level=0.05). # RESULTS Reliability ranged from fair to almost perfect (kappa) for Deep Squat (0.61 Day 1, 0.79 Day 2), Shoulder Mobility (0.90 Day 1, 1.00 Day 2), Active Straight Leg Raise (0.53 Day 1, 0.69 Day 2), and Trunk Stability Push Up (0.48 Day 1, 0.49 Day 2) on both testing occurrences (p\<0.05). Reliability (kappa) was fair for Inline Lunge (0.24 Day 1, 0.39 Day 2), and poor for Hurdle Step (Day 1 -0.01, Day 2 no result) and Rotary Stability (Day 1 -0.03, Day 2 -0.01). Results for Krippendorff's α were similar, with unacceptable interrater reliability for Hurdle Step (Day 1 -0.01, Day 2 1.00), Inline Lunge (Day 1 0.31, Day 2 0.39), and Rotary Stability (Day 1 -0.02, Day 2 -0.01). Interrater composite score reliability (ICC) was good (0.79 Day 1, 0.84 Day 2; both p\<0.05). # CONCLUSIONS Findings suggest that a brief training seminar may be sufficient to ensure acceptable reliability in many, but not all, of the FMS™ component tests and composite score. # Levels of Evidence Level 2b